Supplementation of Arabian jujube (Ziziphus spina Christi) leaf extracts as extender material on the quality of Bali bull semen - Sahiruddin; Widjiati; Toleng, A L; Yusuf, M; Masturi (IOP conference series. Earth and environmental science, 2020)
Semen is subject to experience a decrease in the quality including motility of the sperms. Decreasing the quality of semen begins during collecting process and continues at the processing stage. Low quality of semen will have an impact on the low fertilization rate, so that efforts are needed to maintain the quality of semen. This is thought to be caused by oxidative reactions that are triggered by free radical activity. Some active ingredients in the Arabian jujube leaf are thought to function as natural antioxidants. This study aimed to determine the effect of supplementation of Arabian jujube leaf extracts (Ziziphus spina Christy) on sperms motility in an effort to maintain the quality of Bali bull fresh semen. This study was conducted at the Laboratory of Animal Reproduction; Semen Processing Unit, Faculty of Animal Science, Hasanuddin University, Makassar. The Arabian jujube leaf extracts was added in the extender at three different treatments; P1 (1%), P2 (3%), P3 (5%) and P0 (control). The results of this study showed that there were different motility of the sperms after supplementing the extender with Arabian jujube leaf extracts. The sperms motility of Bali bull semen at concentration of 5% during five days equilibration at 5°C had higher than 3%, 1%, and control, respectively (50.0 vs. 48.7, 43.8, and 46.3%). It can be concluded that supplementation of Arabian jujube leaf extract in the extender material could maintain the quality of Bali bull semen.